Strategi Meningkatkan Seat Load Factor pada Penerbangan Citilink - Sarinah Sarinah; Mariyatul Qibtiyah; Siti Nurhayati (Institut Transportasi dan Logistik Trisakti, 2019)
PT Citilink Indonesia is one of the low cost airlines or Low Cost Carrier (LCC), a subsidiary of PT Garuda Indonesia (Persero). The problem discussed in this study was how to increase the number of seat load factors of PT Citilink Indonesia. The purpose of this study is to determine the company's internal and external factors and to analyze the strategies formulation to increase the number of seat load factors of Kertajati - Surabaya route in 2019. The research method used in this study was Qualitative by obtaining data through interviews and questionnaires. Based on the results of the Internal External Matrix (IE), the company's position is in cell I; growth and development, with a total score of internal factors of 3.12 and external factors of 3.12. The alternative strategies could be applied are market penetration, market development, and product development. While based on SWOT - 4K analysis using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) tables, the internal strength factor is 3.78 and the weakness factor is 2.27, which shows the difference between the two internal factors is 1, 41. As for the external factor the chance is 3.24 and the threat is 3.00, which shows the difference between the two external factors is 0.24. The conclusion of the research based on SWOT-4K diagram the company's position is in the SO quadrant, where the company has great strength and opportunities and based on SWOT-4K Matrix the company's position is in the S-O strategy.